MEASURING THE SUCCESS OF INDUSTRIAL INTERNSHIP PROGRAMME FOR UNDERGRADUATE STUDY - Abdul Karim, Z. A. (2009)
Universiti Teknologi PETRONAS (UTP), Malaysia has made the industrial internship program as an integral part of its undergraduate academic curriculum since the beginning of the formation of the university in 1997. All students from the engineering and technology faculties must undergo an eight-month (32 weeks) industrial internship at selected training providers or host companies prior to the completion of studies. UTP has recognised that providing working exposure to students not only enhances their understanding of the theoretical knowledge but also prepares them to meet the global expectations of the industry upon graduation.This paper presents the evaluations constructed to measure the achievement of UTP’s industrial internship program in developing well-rounded graduates. The evaluations were made through a series of questionnaires from students of various disciplines and supervisors of the organisation. Statistical procedures were used to analyse the collected data. The results from a survey conducted from 40 students from the Computer and Information Science Department in 2002 indicated that the students are able to cope confidently with the technicality of the problems for a given assignment and have acquired the necessary soft skills. Another survey through questionnaires with a responds of 247 and 321 out of 387 distributed to students and supervisors respectively, in 2006 showed that the students rated highly on the experience and skills gained during the industrial internship. The results also found that the training providers were very supportive in the training program and provided authentic job experience to the students. Responses from the industry supervisors show a rating of “good” and “excellent” on the understanding the job, job performance, quality of work and acquisition of soft skill competencies.